2023
DOI: 10.5194/egusphere-2023-433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between marine aerosol optical properties and wind fields over remote oceans with use of spaceborne lidar observations

Abstract: Abstract. By utilizing Level 2A products (particle optical properties and numerical weather prediction data) and Level 2C products (numerical weather prediction wind vector assimilated with observed wind component) provided by the Atmospheric Laser Doppler Instrument (ALADIN) onboard the Aeolus mission, and Level 2 vertical feature mask (VFM) products provided by Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) onboard Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) mission… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Although CALIPSO retrievals of surface wind speeds have been used in many studies (e.g., Hu et al, 2008;Josset et al, 2010a;Josset et al, 2010b;Kiliyanpilakkil and Meskhidze, 2011;Nair and Rajeev, 2014;Murphy and Hu, 2021;Sun et al, 2023), the main drawback is that one must have an accurate calibration of the measured ocean surface reflectance. This presents a difficulty for elastic backscatter lidars like CALIPSO, for which the signal is typically calibrated high in the atmosphere where molecular backscatter dominates and aerosol backscatter is insignificant or can be accurately estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Although CALIPSO retrievals of surface wind speeds have been used in many studies (e.g., Hu et al, 2008;Josset et al, 2010a;Josset et al, 2010b;Kiliyanpilakkil and Meskhidze, 2011;Nair and Rajeev, 2014;Murphy and Hu, 2021;Sun et al, 2023), the main drawback is that one must have an accurate calibration of the measured ocean surface reflectance. This presents a difficulty for elastic backscatter lidars like CALIPSO, for which the signal is typically calibrated high in the atmosphere where molecular backscatter dominates and aerosol backscatter is insignificant or can be accurately estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ALADIN's Level-2 backscatter and extinction coefficients are subject to independent Quality Control (QC) procedures. Despite these challenges, it has been demonstrated that ALADIN is capable of retrieving lidar ratios from smoke (Baars et al, 2021), dust (Flament et al, 2021) and marine aerosols (Sun et al, 2023).…”
mentioning
confidence: 99%